Meningkatkan Ketarampilan Menulis Cerpen Pada Pembelajaran Bahasa Indonesia dengan Menggunakan Media Audio Visual - Dzikri Maulana Gumilar Fazdhan; Rifki Arif Nugraha; Yeni Sulaeman; Ade Farid (KRAKATAU (Indonesian of Multidisciplinary Journals), 2023)
ABSTRACT The method used in this research is collaborative classroom action research (CAR). Researchers collaborate with teachers to plan, identify, observe, and carry out the actions that have been designed. The research design used was a spiral system class action research with the Hopkins and John Eliot models which began with preliminary actions then continued with planning, action, observation, and reflection. The research was conducted in 2 cycles. The research was carried out at SDN Rocek 3, Rocek Village, Cimanuk District, Pandeglang Regency, Sempel selected in this study were class VI students, totaling 24 students consisting of 16 boys and 8 girls. In this study there were several stages carried out from pre-cycle research, cycle I, and cycle II The results of this study revealed that in the pre-cycle conditions, students who had completed learning were 9 students, about 37% of 24 students with a class average of 37.5 after carrying out activities in cycle I, the number of students who had completed learning became 14 students from 24 students or about 58% with an average value of 73.83. In cycle II, it is known that there are 21 students out of 24 students who have successfully completed their studies, obtaining an average score of 8208.33 with a completeness percentage of 87% and can be said to be successful. The background to the increase in student learning outcomes in Indonesian language short story writing material is the use of effective and fun learning media so that it can motivate students' interest in learning to be even better. The learning media used is audio-visual learning media. Keywords: Learning Outcomes, Indonesian Language Learning, Short Story Writing Material, Audio-Visual Media.